2007
DOI: 10.1093/bioinformatics/btm113
|View full text |Cite
|
Sign up to set email alerts
|

DPTF: a database of poplar transcription factors

Abstract: The database of poplar transcription factors (DPTF) is a plant transcription factor (TF) database containing 2576 putative poplar TFs distributed in 64 families. These TFs were identified from both computational prediction and manual curation. We have provided extensive annotations including sequence features, functional domains, GO assignment and expression evidence for all TFs. In addition, DPTF contains cross-links to the Arabidopsis and rice transcription factor databases making it a unique resource for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 12 publications
(10 reference statements)
1
56
0
Order By: Relevance
“…In an attempt to demonstrate the reliability of the identified genes, keyword search with NAM against NCBI nucleotide database was performed, resulting in 153 members which were all included in the NACs identified above. In comparison to the NAC gene family in PlnTFDB http://plntfdb.bio.uni-potsdam.de/v3.0/[3] and DPTF http://dptf.cbi.pku.edu.cn/[58], in which 167 and 172 members were proposed respectively, the 170 gene loci revealed in the present study were roughly in agreement with the former. Then, the discrepancy loci identified in our studies with the two databases mentioned above were further scrutinized to see if any misannotations were inferred.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In an attempt to demonstrate the reliability of the identified genes, keyword search with NAM against NCBI nucleotide database was performed, resulting in 153 members which were all included in the NACs identified above. In comparison to the NAC gene family in PlnTFDB http://plntfdb.bio.uni-potsdam.de/v3.0/[3] and DPTF http://dptf.cbi.pku.edu.cn/[58], in which 167 and 172 members were proposed respectively, the 170 gene loci revealed in the present study were roughly in agreement with the former. Then, the discrepancy loci identified in our studies with the two databases mentioned above were further scrutinized to see if any misannotations were inferred.…”
Section: Resultssupporting
confidence: 81%
“…Hidden Markov Model (HMM) profile of NAC domain (PF02365) downloaded from Protein family (Pfam) http://pfam.sanger.ac.uk/ was exploited for the identification of the NAC genes from Populus genome using HMMER (v 2.3.2) [89]. All non-redundant hits with expected values less than 1.0 were collected and then compared with the NAC family in PlnTFDB http://plntfdb.bio.uni-potsdam.de/v3.0/[3] and DPTF http://dptf.cbi.pku.edu.cn/[58]. As for the incorrectly predicted genes, manual reannotation was performed using online web server FGENESH http://linux1.softberry.com/berry.phtml[59].…”
Section: Methodsmentioning
confidence: 99%
“…The actual number of genes in our data set is between 2,513 (the minimum number of genes) and 2,882 (the total number of sequences). This value is greater than the predicted number of TFs present in Arabidopsis (1,922) and rice (O. sativa indica, 2,025, O. sativa japonica, 2,384; Guo et al, 2005Guo et al, , 2006 and equivalent to that reported in poplar (2,576; Zhu et al, 2007). N. tabacum is considered to be an ancient allotetraploid (2n 5 4x 5 48) resulting from an interspecific hybridization event between Nicotiana sylvestris and Nicotiana tomentosiformis (Goodspeed, 1954;Murad et al, 2002).…”
Section: Tfs In the Tobacco Genomementioning
confidence: 58%
“…Seven of the nine largest TF gene families in tobacco are very similar in size and complexity to their counterparts in Arabidopsis, rice, and poplar (Guo et al, 2005;Gao et al, 2006;Zhu et al, 2007). This allowed us to identify possible functional homologs in tobacco of genes characterized in other plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation